2018
DOI: 10.1002/app.46734
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin incorporated PVA‐borax dual delivery hydrogels as potential wound dressing materials—Correlation between viscoelastic properties and curcumin release rate

Abstract: Poly(vinyl alcohol) (PVA) is a biocompatible polymer which can be physically crosslinked by Borax to form hydrogel. PVA‐Borax (PB) hydrogel is a promising candidate for drug delivery system. Therefore, it is necessary to find the quantitative relationship between drug release rate and network structure of PB hydrogels to predict and control drug release rate. In this work, at first step the optimum ratio of Borax: PVA was determined by studying the interactions between PVA chains and Borax molecules by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…Drug release mechanism showed in initial stages drug diffusion of curcumin loaded Pluronic micelles followed by erosion of hydrogel matrix at later stages. This drug delivery vehicle can be used as a competent wound dressing [148] . PVA/starch/citric acid based composite films for wound dressing applications were studied by Das et al The findings showed that the prepared polymer films present improved water vapor transmission rate and antibacterial activity against Gram-negative ( E. coli ) and Gram-positive ( L. monocytogenes ) bacteria [149] .…”
Section: Biomaterials For Wound Managementmentioning
confidence: 99%
“…Drug release mechanism showed in initial stages drug diffusion of curcumin loaded Pluronic micelles followed by erosion of hydrogel matrix at later stages. This drug delivery vehicle can be used as a competent wound dressing [148] . PVA/starch/citric acid based composite films for wound dressing applications were studied by Das et al The findings showed that the prepared polymer films present improved water vapor transmission rate and antibacterial activity against Gram-negative ( E. coli ) and Gram-positive ( L. monocytogenes ) bacteria [149] .…”
Section: Biomaterials For Wound Managementmentioning
confidence: 99%
“…Rezvan and co-workers formulated curcumin-loaded Pluronic F127 nanomicelles encapsulated PVA-borax dual delivery polymeric hydrogels for wound dressing. The in vitro drug release studies using UV-vis spectroscopy analysis demonstrated that these hydrogels are appropriate scaffolds for curcumin delivery for wound healing applications [ 75 ]. Juan and co-workers synthesized hydrogels loaded with gelatin microsphere containing curcumin nanoparticles for diabetic wound healing.…”
Section: Curcumin-loaded Wound Dressingsmentioning
confidence: 99%
“…When hydrogel structures are sunk in water, they are not dissolved because crosslinked structures hold all molecules together and water molecules are filled and accumulated among cross-linked molecules and hydrogels can retain water more than their dried weight [3]. Polyvinyl alcohol (PVA) is considered a biocompatible polymer and can be crosslinked by different crosslinking agents including borax, glutaraldehyde (GA), and maleic anhydride [47]. Preparation and various applications of PVA-based hydrogels by using different crosslinkers have been studied and reported in the literature.…”
Section: Introductionmentioning
confidence: 99%